2021
DOI: 10.1002/agj2.20724
|View full text |Cite
|
Sign up to set email alerts
|

Science‐based maize stover removal can be sustainable

Abstract: Maize (Zea mays L.) stover can be harvested for multiple uses or left in the field to sustain soil organic carbon (SOC), cycle essential plant nutrients, and protect soil health. This 13-year field study quantified effects of no (0 Mg ha -1 y -1 ), low (1.0 to 1.4 Mg ha -1 y -1 ), moderate (3.5 to 4.0 Mg ha -1 y -1 ), or high rates (4.7 to 5.4 Mg ha -1 y -1 ) of stover harvest from either continuous maize or maizesoybean [Glycine max. (L.) Merr.] rotation on grain yield, plant nutrient concentrations, and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…N management scenarios included two fertilization strategies, in the early spring or pod development stage ( Mourtzinis et al, 2018 ), and a high/low initial soil inorganic N to reflect different amounts of leftover N from the previous maize crop, within the ranges reported by Martinez-Feria et al (2019) . Residue management scenarios included alterations in the residue amount ( Nunes et al, 2021 ) and CN ratio ( Burgess et al, 2011 ). We also considered a scenario with a full tillage event before sowing ( Daigh et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…N management scenarios included two fertilization strategies, in the early spring or pod development stage ( Mourtzinis et al, 2018 ), and a high/low initial soil inorganic N to reflect different amounts of leftover N from the previous maize crop, within the ranges reported by Martinez-Feria et al (2019) . Residue management scenarios included alterations in the residue amount ( Nunes et al, 2021 ) and CN ratio ( Burgess et al, 2011 ). We also considered a scenario with a full tillage event before sowing ( Daigh et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several other recent Iowa studies in continuous corn have also reported grain yield increases with stover harvest. For instance, Nunes et al (2021) reported an average 4.5% increase in grain yield over 13 years with moderate stover removal rates, but no yield impacts at high stover removal rates Possible reasons for the yield increases sometimes observed with stover removal include darker soils that speed soil warming and corn phenological development in the spring (Sindelar et al, 2013), and greater levels of plantavailable nitrogen due to less immobilization by crop residues (Pantoja et al, 2015).…”
Section: Stover-harvest Compaction Was Minimal With No Grain Yield Im...mentioning
confidence: 99%
“…Nunes et al (2021) recommended planning stover harvest based on expected yields: for tilled fields without cover crops, they recommended harvesting stover only when grain yields exceed 12 Mg ha −1 , with stover removal not to exceed 25%-40% of aboveground biomass. Nunes et al (2021) further recommended grain yields average a critical value of 11 Mg ha −1 for systems with implementation of soil health practices, including no-till, extended crop rotations, or cover crops. These recommendations were based principally on concerns for avoiding soil erosion and nutrient losses.…”
Section: Implementing No-till Following Stover Harvestmentioning
confidence: 99%
See 1 more Smart Citation
“…However, successful ICLS design is constrained by limited information on belowground competitive and complementary interactions among species (Jose et al., 2006). In particular, root growth can improve soil health by altering the soil structure (Nunes et al., 2021), and thus quantitative data on the interactions of root systems in ICLS would help reveal when and how competition for resources occurs among the fine roots of different species and the aboveground effect of these interactions (Sarto et al., 2020a).…”
Section: Introductionmentioning
confidence: 99%